2014
DOI: 10.1016/j.juro.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

5-Year Outcome of a Randomized Prospective Study Comparing bacillus Calmette-Guérin with Epirubicin and Interferon-α2b in Patients with T1 Bladder Cancer

Abstract: Bacillus Calmette-Guérin was more effective than the tested combination therapy. The currently recommended management with second resection and 3-week maintenance bacillus Calmette-Guérin entails a low risk of cancer specific death. More aggressive treatment in patients with infiltrative tumors at second resection might improve these results. In particular, concomitant carcinoma in situ was not a predictive factor for poor outcome after bacillus Calmette-Guérin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 15 publications
2
33
0
2
Order By: Relevance
“…In our cohort, the 5-year RFS rate was 65%, which is in concordance with current literature with rates ranging between 59 and 69% with the other strains [16,21,25]. Similar, the 5-year PFS rate of 81% is in line with recent studies reporting rates between 72 and 84% with other strains [25,26,27,28,29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our cohort, the 5-year RFS rate was 65%, which is in concordance with current literature with rates ranging between 59 and 69% with the other strains [16,21,25]. Similar, the 5-year PFS rate of 81% is in line with recent studies reporting rates between 72 and 84% with other strains [25,26,27,28,29].…”
Section: Discussionsupporting
confidence: 92%
“…Similar, the 5-year PFS rate of 81% is in line with recent studies reporting rates between 72 and 84% with other strains [25,26,27,28,29]. …”
Section: Discussionsupporting
confidence: 91%
“…2 Numerous investigations have been conducted regarding reduction of adverse effects while maintaining or improving tumor control, for example, antibiotic prophylaxis, concurrent use of interferon, and dose reduction. 3,24,25 Dose reduction is one of the most investigated methods for reducing the side effects of BCG instillation. Most studies have suggested that dose reduction could significantly reduce the incidence of side effects without compromising treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published randomized controlled trial [ 28 ] of interferon with epirubicin compared to BCG for treatment after resection of HG T1 UCB found a signifi cantly lower 5-year recurrencefree survival rate for those treated with the combined interferon/epirubicin compared to BCG (38 % vs. 59 %, respectively).…”
Section: Resultsmentioning
confidence: 99%